2019
DOI: 10.1016/j.celrep.2019.08.048
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptic Organization of Layer 6 Circuits Reveals Inhibition as a Major Output of a Neocortical Sublamina

Abstract: Graphical Abstract Highlights d Distinct circuits in upper and lower layer 6a distinguish two functional sublayers d Interlaminar inhibitory neurons reside in a specialized sublayer in upper layer 6a d Interlaminar interneurons integrate both local and thalamic inputs d Interlaminar inhibitory projections contribute to the canonical cortical microcircuit SUMMARYThe canonical cortical microcircuit has principally been defined by interlaminar excitatory connections among the six layers of the neocortex. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 109 publications
13
92
1
Order By: Relevance
“…This suggests that much of the tonic activity of deep layer PV cells is driven by interhemispheric input. Deep layer interneurons have recently been shown to project axons through all cortical layers toward the pia (Bortone et al, 2014;Frandolig et al, 2019). It is possible that interlaminar projections from deep layer PV interneurons mediate the indirect network effects underlying principal cell excitation following withdrawal of callosal input.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that much of the tonic activity of deep layer PV cells is driven by interhemispheric input. Deep layer interneurons have recently been shown to project axons through all cortical layers toward the pia (Bortone et al, 2014;Frandolig et al, 2019). It is possible that interlaminar projections from deep layer PV interneurons mediate the indirect network effects underlying principal cell excitation following withdrawal of callosal input.…”
Section: Discussionmentioning
confidence: 99%
“…Even within the population of L6 CT pyramidal cells, there are at least 2 subtypes defined by morphology [87][88][89], 3 subtypes defined by electrophysiology and morphology [89], and and carnivores, where feedforward processing along the retino-geniculo-cortical pathway occurs in functionally segregated, parallel pathways, CT feedback circuits seem to mimic this organization, both in terms of morphology [90,91] and function [92] [99]. Instead, a crucial element to produce gain modulations seems to be changes in the level of synaptically driven V m fluctuations, often called "synaptic noise" [100][101][102].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous work has shown that L6 Ntsr1 neurons receive a large portion of their anatomical input from long-range projection neurons (Vé lez-Fort et al, 2014). L6 Ntsr1 neurons also receive less thalamic input, especially deep Ntsr1 neurons (Frandolig et al, 2019), compared with intracortical L6a neurons and L4 neurons (Crandall et al, 2017;Wang et al, 2013). In light of these comparisons, the overlap between Ntsr1 and Drd1 L6b neurons is unknown but may be an important consideration.…”
Section: Methodsological and Comparative Considerationsmentioning
confidence: 99%